2016
DOI: 10.3389/fmed.2016.00064
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Coagulation and Fibrinolysis in Acute Respiratory Distress Syndrome: A Prospective Pilot Study

Abstract: IntroductionCoagulation and fibrinolysis remain sparsely addressed with regards to acute respiratory distress syndrome (ARDS). We hypothesized that ARDS development might be associated with changes in plasma coagulation and fibrinolysis. Our aim was to investigate the relationships between ARDS diagnosis and plasma concentrations of tissue factor (TF), tissue plasminogen activator (t-PA), and plasminogen activator inhibitor-1 (PAI-1) in mechanically ventilated patients at increased risk of developing ARDS.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 40 publications
3
58
2
Order By: Relevance
“…Nonetheless, an excessive inhibition of procoagulant factors might also be deleterious, as was observed by Basterache et al, who suggested that the complete deficiency of TF in an ALI model lead to an increase of intra‐alveolar hemorrhage. In contrast, other studies indicate that high levels of TF result in higher depositions of fibrin, which is associated with a worst outcome . In our results, nebulized anticoagulants reduced TF levels but not completely, attenuating lung coagulopathy and fibrin deposition in the lungs without producing intra‐alveolar hemorrhage.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Nonetheless, an excessive inhibition of procoagulant factors might also be deleterious, as was observed by Basterache et al, who suggested that the complete deficiency of TF in an ALI model lead to an increase of intra‐alveolar hemorrhage. In contrast, other studies indicate that high levels of TF result in higher depositions of fibrin, which is associated with a worst outcome . In our results, nebulized anticoagulants reduced TF levels but not completely, attenuating lung coagulopathy and fibrin deposition in the lungs without producing intra‐alveolar hemorrhage.…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast, other studies indicate that high levels of TF result in higher depositions of fibrin, which is associated with a worst outcome. 40,41 In our results, nebulized anticoagulants reduced TF levels but not completely, attenuating lung coagulopathy and fibrin deposition in the lungs without producing intra-alveolar hemorrhage.…”
Section: Discussionmentioning
confidence: 50%
“…Some experimental evidence has revealed that abnormalities in the pro-coagulation and fibrinolysis protein pathways are features of ALI [23,24]. ALI is accompanied by fibrin deposition in the lung and increased plasminogen activator inhibitor expression in bronchoalveolar lavage (BAL) fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the coagulation system has been shown to be relevant in the pathogenesis of ARDS. Ozoline et al demonstrated that median plasma concentrations of tissue factor and plasminogen activator inhibitor‐1 were significantly higher at day seven in patients with ARDS, as compared to non‐ARDS 12 . The mechanisms contributing to this lung coagulopathy are localized tissue factor‐mediated thrombin generation, and depression of bronchoalveolar plasminogen activator‐mediated fibrinolysis, mediated by the PAI‐1 increase.…”
Section: Figurementioning
confidence: 99%
“…The mechanisms contributing to this lung coagulopathy are localized tissue factor‐mediated thrombin generation, and depression of bronchoalveolar plasminogen activator‐mediated fibrinolysis, mediated by the PAI‐1 increase. 12,13 Treatment with heparin may thus be helpful in mitigating this pulmonary coagulopathy. A meta‐analysis noted that adjunctive treatment with LMWH within the initial 7‐day onset of ARDS reduces the risk of 7‐day mortality by 48% and the risk of 28‐day mortality by 37% in addition to significantly improving PaO2/FiO2 ratio (the improvement is particularly important in the subgroup receiving high‐dose LMWH of ≥ 5000 units/d) 14 .…”
Section: Figurementioning
confidence: 99%